INTELLIGENT DIGITAL ON BOARDING (Proceedings of the International Conference on Public Health, 2017)
In last few decades on boarding has been evolved from paper based approach to paper less approach and today on boarding can be done anywhere any time with any device. With the emergence of technology and availability of internet on boarding process becomes quite easy. But most of the time patient ends up providing non contextual information. Existing on boarding services give similar experience to all patients despite their age, gender and complaints. This paper is proposing a context aware digital on boarding solution for the patients to personalize patient’s on boarding experience. Proposed solution understands patient’s context with the help of workflow based questionnaire. Basis of questionnaire is patient’s gender, complaint and age group. This solution generates summary based on the patient’s response and publish summary which can help doctors in diagnosing the problem. This solution can be integrated to the existing hospital information system to provide better on boarding experience to the patients. Health Research Institutes can do health behaviors analysis of patients using data collected by system. This solution can be used by health workers in remote areas to understand the patient’s problem by asking contextualized questions populated by the system and hence they can provide primary care to the patient.
Keywords: digital on boarding, context aware intelligence, work flow based questionnaire, natural processing language